AN EDUCATIONAL PROPOSAL FOR A GROUP COUNSELING PROJECT FOR MIDDLE SCHOOL PUPILS - Marius Costel ESI (Association of Social and Educational Innovation, 2023)
The existence of a contradictory reality at the social and educational level reveals the need to consider the idea of counseling at the group level in an appropriate organizational environment. The (re)discovery of such a reality highlights the correspondence and interdependence among some components associated with the counseling field. Therefore, within the framework of this project, we intend to make the approaches of an educational and also of a scientific nature more efficient in relation to the field of counseling at group level.